Current (European) Developments in Scholarly Communication - Prosser, David C. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
Any paper describing new developments in open access policies and mandates risks being out-of-date almost before it is finished. New policies from governments, research funding bodies, and individual institutions around the world are announced weekly. This paper attempts to describe some of the most recent and important policies and mandates, and puts these policies into the context of wider social pressures on scholarly communication. Finally, the papers attempts to sketch some of the ways in which the library community can react to the changing scholarly communication environment.